A review of economic issues for gene‐targeted therapies: Value, affordability, and access. Issue 1 (28th February 2023) - Garrison, Louis P.; Lo, Andrew W.; Finkel, Richard S.; Deverka, Patricia A.
Abstract: The National Center for Advancing Translational Sciences' virtual 2021 conference on gene‐targeted therapies (GTTs) encouraged multidisciplinary dialogue on a wide range of GTT topic areas. Each of three parallel working groups included social scientists and clinical scientists, and the three major sessions included a presentation on economic issues related to their focus area. These experts also coordinated their efforts across the three groups. The economics‐related presentations covered three areas with some overlap: (1) value assessment, uncertainty, and dynamic efficiency; (2) affordability, pricing, and financing; and (3) evidence generation, coverage, and access. This article provides a synopsis of three presentations, some of their key recommendations, and an update on related developments in the past year. The key high‐level findings are that GTTs present unique data and policy challenges, and that existing regulatory, health technology assessment, as well as payment and financing systems will need to adapt. But these adjustments can build on our existing foundation of regulatory and incentive systems for innovation, and much can be done to accelerate progress in GTTs. Given the substantial unmet medical need that exists for these oft‐neglected patients suffering from rare diseases, it would be a tragedy to not leverage these exciting scientific advances in GTTs.